High expression of small GTPase Rab3D promotes cancer progression and metastasis - Yang, Jian (Oncotarget, 2015)
Rab GTPases control exocytic and endocytic membrane trafficking such as exosomes release. As a secretory small GTPase, Rab3D is a vital regulator for protein secretion. However, the role of Rab3D in cancer was never systematically studied. The aim of this study is to examine its function and mechanism in cancer, especially metastasis. We detected protein levels of Rab3D in nine cancer cell lines and twelve types of clinical cancer specimens. Subsequently, we established in vitro migration and in vivo orthotopic metastatic mouse models to study the role of Rab3D in tumor metastasis. Here, we reported that the expression levels of Rab3D were dysregulated in cancer cells and highly correlated with tumor malignancies in the clinical samples. Increased expressions of Rab3D led to tumor invasion in vitro and lung metastasis in vivo, whereas Rab3D knockdown suppressed the tumor cell motility. Mechanistic studies revealed that Rab3D activated intracellular the AKT/GSK3β signaling to induce the EMT process. In addition, it also regulated the extracellular secretion of Hsp90α to promote tumor cell migration and invasion. These results prove that Rab3D is a key molecule to regulate tumor metastasis, suggesting that blocking the Rab3D function can be a potential therapeutic approach for cancer metastasis.